Social Institutions, Imperfect Information, and the Distribution of Income: A Comment - Lazonick, William H. (Quarterly Journal of Economics, 1978)
Journal Article Social Institutions, Imperfect Information, and the Distribution of Income: A Comment Get access William H. Lazonick William H. Lazonick Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 92, Issue 1, February 1978, Pages 179–184, https://doi.org/10.2307/1886005 Published: 01 February 1978